2022
DOI: 10.2147/jmdh.s337250
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tranexamic Acid in Cancer Surgery. An Update of Clinical Findings and Ongoing Research

Abstract: In cancer patients undergoing surgery, tumor biology and anticancer treatments can increase the risk of perioperative bleeding and blood transfusions. Notably, blood transfusions can be potentially associated with an increased risk of life-threatening immune responses, acute lung injury, postoperative infections, and thromboembolism. Moreover, the link between perioperative transfusion and increased risk of cancer recurrence cannot be excluded. On the other hand, cancer patients have an increased risk of throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Again, this could be explained by TXA-mediated inhibition of the fibrinolytic cascade and its immunomodulatory effects, resulting in reduced infection rates as seen in the cardiac surgery literature. 20,21,23,24 However, like a retrospective review of TXA use in breast reduction patients conducted by Weissler et al, 19 we found no significant impact on seromas and hematomas with TXA use. In accordance with the literature, we found no significant increase in overall complications from TXA use.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Again, this could be explained by TXA-mediated inhibition of the fibrinolytic cascade and its immunomodulatory effects, resulting in reduced infection rates as seen in the cardiac surgery literature. 20,21,23,24 However, like a retrospective review of TXA use in breast reduction patients conducted by Weissler et al, 19 we found no significant impact on seromas and hematomas with TXA use. In accordance with the literature, we found no significant increase in overall complications from TXA use.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, no patients developed suture granulomas in the TXA group in comparison to 5 patients in the non- TXA group. Again, this could be explained by TXA-mediated inhibition of the fibrinolytic cascade and its immunomodulatory effects, resulting in reduced infection rates as seen in the cardiac surgery literature 20,21,23,24 . However, like a retrospective review of TXA use in breast reduction patients conducted by Weissler et al, 19 we found no significant impact on seromas and hematomas with TXA use.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this sense, only tranexamic acid (TXA) showed a good value of AUC (0.81) in the ROC analysis. TXA has been reported to prevent blood clot breakdown and thus bleeding since it is an analog of lysine which blocks the interaction with brin and the conversion of plasminogen to plasmin [22]. Also, a family of compounds related with 4-(3-pyridyl)-butanoic acid such as 4-hydroxy-4-(3-pyridyl)butanoic acid are considered potent carcinogenic compounds related with tobacco [23].…”
Section: Metabolite Alterations In Pre Posta and Postb Compared With ...mentioning
confidence: 99%
“…Currently, the literature regarding TXA utilization for neoplastic diseases of the lower extremity is limited to three studies 13–15 . As such, orthopedic oncologic surgeons may be hesitant to administer IV TXA before surgery for neoplastic pathologic fractures of the lower extremity due to the concern that the antifibrinolytic properties of TXA inhibiting clot dissolution may exacerbate the risk of VTE in these hypercoagulable individuals 13,14,16,17 . Thus far, this has yet to be proven.…”
Section: Introductionmentioning
confidence: 99%